Pomiędzy ekonomią a ochroną zasobów: gospodarowanie gruntami rolnymi na wybranych przykładach w gminie Zbąszyń (Wielkopolska) - Markuszewska, Iwona; Marchewka, Paulina (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2016)
Rural areas are more often exposed to changes as a result of the urbanisation of the countryside. As a consequence, changes in the agricultural land use are observed, which often lead to the loss of the soil’s resources. Reconciling the development of rural areas with the dynamics of the transformation of rural areas as a result of the suburbanisation process is s very difficult task to accomplish. This is why rational management of agrarian production space is important at local level. This paper presents the issue of the de-farming of agricultural land using the example of the Zbąszyń Commune in the Wielkopolska Region.
Keywords: agricultural production space; de-farming; sustainable development of rural areas; Zbąszyń Commune